Profile of guanfacine extended release and its potential in the treatment of attention-deficit hyperactivity disorder - Martinez-Raga J (Dove Medical Press, 2015)
Jose Martinez-Raga,1,2 Carlos Knecht,3 Raquel de Alvaro4 1Teaching Unit of Psychiatry and Psychological Medicine, University Hospital Doctor Peset, University of Valencia, 2CEU Cardenal Herrera University, 3Área de Salud Mental, Hospital Padre Jofré, Valencia, 4Hospital General, Consorcio Hospitalario Provincial, Castellon, Spain Abstract: The α2-adrenergic receptor agonist guanfacine, in its extended-release formulation (GXR), is the most recent nonstimulant medication approved in several countries for the treatment of attention-deficit hyperactivity disorder (ADHD) as monotherapy and as adjunctive pharmacotherapy to stimulants in children and adolescents. The present paper aims to review comprehensively and critically the pharmacodynamic and pharmacokinetic characteristics and the published evidence on the efficacy and safety profile of GXR in the treatment of ADHD. A comprehensive search of relevant databases (PubMed, Embase, and PsycInfo) was conducted to identify studies published in peer-reviewed journals until January 15, 2015. Though the precise mechanism of action of guanfacine in the treatment of ADHD is not fully understood, it is thought to act directly by enhancing noradrenaline functioning via α2A-adrenoceptors in the prefrontal cortex. Weight-adjusted doses should be used, with a dosing regime on a milligram per kilogram basis, starting at doses in the range 0.05–0.08 mg/kg/day, up to 0.12 mg/kg/day. As evidenced in short-term randomized controlled trials and in long-term open-label extension studies, GXR has been shown to be effective as monotherapy in the treatment of ADHD. Furthermore, GXR has also been found to be effective as adjunctive therapy to stimulant medications in patients with suboptimal responses to stimulants. Many of the adverse reactions associated with GXR, particularly sedation-related effects, were dose-related, transient, mild to moderate in severity, and did not interfere with attention or overall efficacy. There are no reports of serious cardiovascular adverse events associated with GXR alone or in combination with psychostimulants. Keywords: guanfacine extended-release, attention-deficit hyperactivity disorder, ADHD, oppositional symptoms, adjunctive therapy, cardiovascular safety